Determinant Factors Affecting the Interest of Gojek Drivers in Using BPJS Ketenagakerjaan in Medan City - Lamsina Harahap; Sri Ramadhani; Fauzi Arif Lubis (Fakultas Ekonomi Universitas Garut, 2026)
The development of the digital economy has driven an increase in the number of informal sector workers who rely on applications, including Gojek drivers who face quite high occupational risks. BPJS Ketenagakerjaan is present as a form of social protection for informal workers, but the participation rate of Gojek drivers in Medan City is still relatively low. This study aims to analyze the influence of income, contribution price, information, and service quality, both partially and simultaneously, on Gojek drivers' interest in joining BPJS Ketenagakerjaan. This study uses a quantitative approach with an explanatory research design. Data were obtained through questionnaires to 100 Gojek drivers in Medan City who are not yet BPJS Ketenagakerjaan participants using a purposive sampling technique. Data analysis was performed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) through the SmartPLS 4.0 application. The results show that income, price, information, and service quality have a positive and significant effect on Gojek drivers' interest in joining BPJS Ketenagakerjaan. The information variable is the most dominant factor, followed by service quality, income, and contribution price. These findings indicate that increasing participation among informal workers is not solely influenced by economic factors, but also by access to information and the quality of services provided. This research is expected to serve as a reference for BPJS Ketenagakerjaan, local governments, and digital platform companies in formulating outreach strategies and improving services to expand social protection coverage for informal workers.